2014
DOI: 10.1002/jsfa.6690
|View full text |Cite
|
Sign up to set email alerts
|

Effects of four different cooking methods on anthocyanins, total phenolics and antioxidant activity of black rice

Abstract: The results indicate that cooking degraded anthocyanins and other phenolic compounds, but with a concomitant increase in phenolics from possible degradation of anthocyanins, which resulted in the enhancement of metal-chelating activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
45
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 25 publications
7
45
0
1
Order By: Relevance
“…This suggest that free phenolic acids in Sinnongheugchal were more stable than those in Sintoheugmi . This result agrees with the result of Surh and Koh () for which the retention of total phenolic compounds after cooking was higher in Sinnongheugchal . Conversely, bound protocatechuic acid and vanillic acid were not significantly changed by any of the cooking methods in both cultivars.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…This suggest that free phenolic acids in Sinnongheugchal were more stable than those in Sintoheugmi . This result agrees with the result of Surh and Koh () for which the retention of total phenolic compounds after cooking was higher in Sinnongheugchal . Conversely, bound protocatechuic acid and vanillic acid were not significantly changed by any of the cooking methods in both cultivars.…”
Section: Resultssupporting
confidence: 93%
“…Interestingly, the sum of the bound phenolic acids in raw Sinnongheugchal (29.90 mg/100 g DW) was also threefold higher compared with the raw Sintoheugmi (8.48 mg/100 g DW). Surh and Koh () found that the anthocyanins content in raw Sintoheugmi was about twofold higher than in the raw Sinnongheugchal . These results suggest that the phenolic acid contents were negatively correlated with those of the anthocyanins in black rice.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations